Benefit from prolonged dose-intensive chemotherapy for infants with malignant brain tumors is restricted to patients with ependymoma: a report of the Pediatric Oncology Group randomized controlled trial 9233/34. Issue 3 (12th December 2013) - Strother, Douglas R.; Lafay-Cousin, Lucie; Boyett, James M.; Burger, Peter; Aronin, Patricia; Constine, Louis; Duffner, Patricia; Kocak, Mehmet; Kun, Larry E.; Horowitz, Marc E.; Gajjar, Amar
Abstract: Background: The randomized controlled Pediatric Oncology Group study 9233 tested the hypothesis that dose-intensive (DI) chemotherapy would improve event-free survival (EFS) for children <3 years of age with newly diagnosed malignant brain tumors. Methods: Of 328 enrolled eligible patients, diagnoses were medulloblastoma ( n = 112), ependymoma ( n = 82), supratentorial primitive neuroectodermal tumor (sPNET, n = 38) and other malignant brain tumors ( n = 96), and were randomized to 72 weeks of standard dose chemotherapy (Regimen A, n = 162) or DI chemotherapy (Regimen B, n = 166). Radiation therapy (RT) was recommended for patients with evidence of disease at completion of chemotherapy or who relapsed within 6 months of chemotherapy completion. Results: Distributions of EFS for Regimens A and B were not significantly different ( P = 0.32) with 2- and 10-year rates of 22.8% ± 3.3% and 15.4% ± 3.7%, and 27.1% ± 3.4% and 20.8% ± 3.8%, respectively. Thus, the study hypothesis was rejected. While distributions of EFS and OS were not significantly different between Regimens A and B for patients with medulloblastoma and sPNET, DI chemotherapy resulted in significantly improved EFS distribution ( P = .0011) (2-year EFS rates of 42.1% vs. 19.6% with SD chemotherapy), but not OS distribution, for patients with centrally confirmed ependymoma. The degree of surgical resection affected EFS, OS or both for most tumor groups. Approximately 20%, 40% and 20% of patients with medulloblastoma, ependymoma treated with DI chemotherapy, and sPNET, respectively appear to have been cured without RT. Of 11 toxic deaths on study, 10 occurred on the DI chemotherapy arm. Conclusions: Prolonged dose-intensive chemotherapy given to infants with malignant brain tumors resulted in increased EFS only for patients with ependymoma.